Obtención de biogás utilizando como base el estiércol de ganado vacuno en la parroquia La Unión, cantón Babahoyo, provincia de Los Ríos - Crespo Troya, Allan Arturo (2020)
Bio digesters are systems designed to optimize the production of biogas from agricultural wastes, excrements of pigs, bovine, goats and humans, as well as industrial effluents, among others, which thus allow obtaining clean and low-cost energy to from a renewable source. The following experimental work was aimed at generating biogas using cattle manure as a base and was carried out on the grounds of La Clementine Farm, La Unión Parish, Babahoyo Canton, with geographical location (UTM) 678189 latitude, 9811027 longitudes. The treatments were randomized in a Random Complete Blocks design with 4 treatments and 5 repetitions, where: T1 was composed of fresh bovine manure (6 lb.) + rice husk (3 lb.) + raw milk (1.5 L) + water (10.5 L). T2, fresh bovine manure (6 lb.) + rice husk (3 lb.) + bread yeast (300 g) + water (10.5 L). T3, fresh bovine manure (6 lb.) + rice husk (3 lb.) + raw milk (1.5 L) + bread yeast (300 g) + water (10.5 L) and T4, bovine manure (6 lb.) + rice husk (3 lb.) + water (13.5 L). The variables evaluated were: biogas production, biol production, discharge pressure, pH and residual organic material. In biogas production, the T2 treatment produced the highest biogas value, however, the treatments did not differ significantly. In the production of biol, treatments T4 and T1 reached 9750 ml and 9620 ml in their order, therefore, the production of biol was not different in all treatments. Similar situation was observed in the pH of the biol, the values varied from 3.9 to 4.4, this difference being not significant in the treatments evaluated. In the discharge pressure, no differences between treatments were obtained. However, the weight of the residual organic matter, it was observed that the T1 with 13.07 lb. had the highest value, being this different to 10.77 lb. and 8.03 lb. obtained in the treatments T3 and T2, respectively. In this context, obtaining biogas as a result of fermentation can present a high production cost during the first months, due to the construction of the reactors and obtaining raw material. Therefore, the production of biogas from cattle manure and agricultural waste can be an advantage for the installation of bio digesters once, from the fermentation of these wastes, clean energy is obtained on a smaller scale, the same as it can be used in internal combustion processes of engines and the byproduct in food production.